Experiences and Perceptions of University Students and General and Special Educator Teacher Preparation Faculty Engaged in Collaboration and Co-Teaching Practices - Leila A Ricci; Joan Fingon (Networks: An Online Journal for Teacher Research, 2018)
General and special education faculty modeling co-teaching practices in teacher preparation programs can promote collaboration among future K-12 teachers serving children with diverse needs. This article describes the experiences and perceptions of 59 university students enrolled in teacher preparation reading courses with sessions co-taught by general education and special education faculty members at a large, Hispanic serving public urban university in Southern California. The courses included lessons on co-planning, co-instructing, and co-assessing in reading jointly taught by the general education and special education professors; class readings and activities on collaboration and co-teaching; and the opportunity for university students to co-plan reading lessons for K-12 students. This mixed method study included pre- and post-student surveys on beliefs about collaboration and co-teaching, and students’ ratings and reflections on the professors’ co-taught sessions. Results showed that university students grew in their knowledge, confidence, and competence in collaboration and co-teaching. General and special education faculty experiences of the process are also shared.
Keywords: co-teaching; collaboration; teacher education; general education; special education